2018
DOI: 10.1111/jopr.12907
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Extended Range Attachment System to Retain Implant Overdentures: A Clinical Report

Abstract: Various attachment systems have been used to facilitate the retention, stability, and support of overdentures. The low profile design, pivoting technology, and durability of the Locator attachment made it one of the commonly used tissue-supported implant-retained overdentures. It has been successfully used to retain overdentures as well as partial dentures. This article describes the uses of the new Locator R-Tx abutment and illustrates both the direct and indirect techniques used to process the denture attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…To connect two implants with overdentures, resilient stud and bar attachments are available. However, the choice of the suitable attachment depends on the arch form, the available prosthetic space, the implant's inclination, and the retention value required (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To connect two implants with overdentures, resilient stud and bar attachments are available. However, the choice of the suitable attachment depends on the arch form, the available prosthetic space, the implant's inclination, and the retention value required (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…When the patient bites, consequently, the inherent space between the patrix and matrix is lost to allow both implant and mucosal support of the denture during function (3,4,9) . However, the amount of occlusal load transmitted by these attachments is a factor of their resiliency that determines their prosthetic complications (10,11,5) . In contrast to Jacobs et al (12,13) a study by Tymstra et al (6) concluded that patients treated with an IROD did not show higher residual ridge resorption (RRR) in anterior maxillary area in comparison to patients used a conventional complete denture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained by reducing the lever arm length resulting in a better mechanical advantage. (13)(14)(15) Easy seating in the oral cavity by the patient, self-aligning feature allow the ability to fit non-parallel implants up to 40° C divergence have been advocated as a suitable alternative to the classical widely used ball attachment. Other studies have reported that the highest retentive force and maintained that force up to 30˚ tilting more in locator attachment system when compared to ball system.…”
Section: Introductionmentioning
confidence: 99%